How the Metaverse Will Reshape Business and Sustainability - El Khoury, Rim.; Alareeni, Bahaaeddin (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Sustainability is part of every aspect of our life, with climate concerns shaping the future. Thus, it is important to understand how metaverse will affect sustainability, as it is opening both challenges and opportunities for environmental sustainability. On the one side, replacing real-world interactions with 3D virtual and exchanging physical goods with digital ones are significantly less resource-intensive and more carbon-efficient. Therefore, this holds the promise of reducing the environmental pollution. On the other side, metaverse increases e-waste and energy consumption. Given this controversial impact, it is crucial for businesses and researchers to understand how to ensure that the metaverse develops sustainably. This book is popping out several questions: Do businesses understand the metaverse concept and perceive the benefits and advantages of implementing such technologies? How will the metaverse change business? Will metaverse change our working place and skills needed? How can companies get ahead of the change and mold it to their advantage? Will businesses use metaverse? Can metaverse create a more sustainable word? How can we make the metaverse better than what we have now? Is it going to affect environmental sustainability? Will it cause more severe climate problems, or would it be the solution? How can metaverse impact the achievements of SDGs?
Demystifying Metaverse in Business: A Conceptual Study -- Relativity of Metaverse in Business Model: A Conceptual Analysis -- An analysis of Future Prospects of Metaverse -- Is Metaverse in Education Blessing in Disguise? -- Are You Ready to Take Avatar in Virtual Classroom - Metaverse in Education from Student's Perspective -- XR and the Metaverse: New Opportunities in Education -- The Role of Accounting Disclosure of Sustainable Development Activities Using Metaverse in The Field of Education and Training -- An Analysis of the Impact of Metaverse on Climate Change -- An Exploratory Study on Metaverse and SDGs -- Opportunities and Risks of the "Metaverse" for Environmental Sustainability -- Metaverse as a Tool for the achievement of SGDs: Challenges, Opportunities and Applications -- Metaverse and Tourism Industry: A Conceptual Proposition -- The Price Determinants of NFTs: The Case of Metaverse -- Role of Metaverse in The Fourth Industrial Revolution for Providing Customer Experiences -- Metaverse and Skill Set: A Conceptual Investigation -- Metaverse Beyond the Hype: Possibilities and Challenges -- Application of Metaverse and Its underlying Challenges in the 21st Century.
Keywords: Sustainability; Bioclimatology; Environmental economics; Electronic commerce; Sustainability; Climate Change Ecology; Environmental Economics; E-Business.